Determination of ruminal nutrient degradability of some feeds and total mixed ration in buffalo using in situ methods - G.H. Mnafiazar; A.T. Yansari; H. Mansouri; B.A. Hamidi (Italian Journal of Animal Science, 2010)
In order to determine of ruminal nutrient degradability of some feeds (wheat straw, alfalfa hay, barley grain, concentrates) and total mixed rations, about 3 g of DM equivalent of samples were weighed in sealed nylon bags (6-cm × 7.5-cm) that were incubated in the rumen of three ruminally fistulated buffalo steers (BW= 389.6 ± 7.5 kg) that fed corn silage and concentrates at maintenance level in a ratio of about 65: 35 (DM basis) according to the following periods 0, 3, 6, 12, 18, 24, 36, 48, 72 and 96 h. Using Cr-mordanated NDF of alfalfa as a single dose marker, ruminal kinetic of digestion were measured. Mean ruminal particulate passage rate (%/h), particulate passage rate in lower compartment on gastrointestinal tract (%/h), ruminal mean retention time (h), mean retention time in lower compartment (h), total mean retention time (h), and delay time of marker were 0.0378, 0.0489, 26.46, 20.45, 56.565 and 9.654, respectively. Dry matter, crud protein, and NDF had similar trend on kinetic of digestion. Barely grain and concentrate had higher degradable fraction (a, b and a + b), rate and extent of degradation and effective degradability. In contrast, forages had lower parameters than others feeds. Barely had the highest degradable DM, NDF, and CP, wheat straw had the lowest degradable DM, NDF, and CP. The lag time of DM and NDF were lowest and highest in barely and wheat straw, respectively. In addition, barely had the highest effective degradability, but wheat straw had the lowest one. It is generally considered that rumen turnover time is slower in buffaloes than in cattle may be a more appropriate indicator of potential ferment ability of feeds in the former species.